Epidemiology of Injuries in Ultimate (Frisbee): A Systematic Review - Diana Fajardo Pulido; Reidar P. Lystad (MDPI AG, 2020)
Ultimate is a high-intensity, non-contact team sport played with a flying disc (e.g., frisbee). Despite the growing popularity of ultimate worldwide, there is limited information about the epidemiology of injury in the sport. The purpose of this review is to provide a comprehensive overview and synthesis of the literature on the epidemiology of injury in ultimate. A comprehensive search of the literature was conducted in five electronic databases (i.e., MEDLINE, Embase, AMED, SPORTDiscus, and AusportMed). All databases were searched from inception to 1 July 2020. A total of eleven studies were included and qualitatively synthesized. Injury incidence rate estimates ranged from 0.4 to 84.9 injuries per 1000 athlete-exposures. The lifetime prevalence of any injury and concussion were 100% and 26%, respectively. The most commonly injured body region was the lower limb, with the knee and thigh being the most frequently injured anatomical locations. The most frequent injury types were muscle injuries and superficial contusions. The most common injury situation was direct contact with another player. There is a substantial risk of injury in ultimate, in particular muscle strains and joint sprains to the knee and shoulder areas. Development and implementation of effective, sport-specific injury prevention initiatives, including improved injury risk management and sport safety culture, should be a priority to reduce the burden of injury in ultimate.